Leadership Style, Climate, Commitment and Corporate Performance - Andreas Budihardjo (UBL, 2013)
The success of a company is dependent on its leader, especially on her or his leadership style, andcommitment. In addition, organizational learning climate might have an influence on its performance.This study attempts to examine the influence of leadership dimensions, affective commitment andorganizational learning climate on corporate performance. In particular, this study aims to find out whichof variables contribute significantly to the corporate effectiveness. This study finds out that affectivecommitment and executor (leadership style) contribute significantly to the corporate performance. Inspite of the fact that learning climate is not correlated significantly with corporate performance, it stillplays an important role as it is significantly correlated with leadership dimensions and affectivecommitment. The samples in this study are experienced senior managers hold an MBA degree; therefore,the generalization of the findings must be carefully taken.